How strong is the case for dollarization in Costa Rica? a note on the business cycle comovements with the United States - Lindenberg, Nannette; Westermann, Frank 1970- (CESifo, 2009)
We evaluate the proposal for official dollarization in Costa Rica by applying a new approach to measure the business cycle comovements with the United States. While the literature often focuses on the correlation of shocks, we point out that the response of each country to the shocks is also an important aspect of stabilization policy. We analyze whether Costa Rica and the United States share a common synchronized response to shocks, i.e. a common business cycle, using the Engle and Kozicki (1993) and Cubadda (1999, 2007) serial correlation common features tests, in a quarterly GDP data set from 1991 to 2008. Although we find some tendency towards common AR(p) structures and common long run trends, we reject the hypothesis that the two countries share a common business cycle. Based on this evidence, we conclude that official dollarization in Costa Rica would impede the efforts of its stabilization policy, despite the relatively high contemporaneous correlation of shocks. -- dollarization ; business cycle comovement ; serial correlation common feature ; Central America, Costa Rica
Parallel als Druckausg. erschienen
Keywords: Dollar; Costa Rica